Knowledge Management and Its Impact on Organizational Agility: An Applied Study on Riyadh Municipality (The International Journal for Scientific Research, 2024)
The study aimed to investigate the impact of knowledge management on organizational agility at the Riyadh Municipality. The study employed a descriptive-analytical methodology, with the researcher developing a questionnaire consisting of 47 items. A total of 103 questionnaires were distributed, and 84 were retrieved, with 76 valid questionnaires for analysis, representing 73.8% of the study population. Data related to the study variables were collected and analyzed using the Statistical Package for the Social Sciences (SPSS).The results indicated that both knowledge management and organizational agility at the Riyadh Municipality were assessed at a moderate level. Furthermore, the results demonstrated a statistically significant impact of knowledge management, including its dimensions (knowledge generation, storage, sharing, and application), on organizational agility at the Riyadh Municipality.The study recommended the necessity of organizing training programs and workshops to familiarize employees at the Riyadh Municipality with various knowledge management processes and their importance in facilitating work procedures and increasing productivity.
Keywords: Knowledge Management; Organizational Agility; Riyadh Municipality